DISKRESI KEPOLISIAN DALAM PENYELESAIAN PERKARA KECELAKAAN LALU LINTAS MELALUI MEDIASI PENAL - Kurniawan, Ramadhi (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
One of the efforts to apply restorative justice by the police in the settlement of trafficaccidents cases is to use penal mediation mechanism as part of the application ofdiscretion as regulated in Article 18 of Law Number 2 Year 2002 concerning Police of theRepublic of Indonesia. The use of discretion by means of penal mediation is possible inminor traffic accidents that the victim usually suffers only material loss. With theincreasing number of traffic accidents, where many accidents cause injuries, both minorinjuries and serious injuries, it can actually be resolved using the peace efforts between theperpetrator and the victim in the mediation of penal based on the authority of the Policefrom the legal settlement through mechanism of criminal justice system.